Іван Франко на сторінках "Kuriera Lwowskiego": щодо слов'янських питань - Шимонік, Д. (Слово і Час, 2020)
У статті проаналізовано тексти І. Франка, присвячені панславізму,
зосібна, слов'янському питанню, які були опубліковані 1888 р. в кількох
випусках «Kuriera Lwowskiego». Письменник і публіцист окреслив дві
різні течії: централістську (московську) і федералістську. Симпатії українського письменника належать останній, що уможливлює
об'єднання слов'янських племен із метою захисту спільних інтересів і
базується на принципі взаємоповаги та збереження традицій кожної національної одиниці. The article deals with the series of texts by Ivan Franko on the subject of panslavism, or more
specifically, the Slavic question, published in 1888 in the several issues of “Kurier Lwowski”.
Franko presents his understanding of the contemporary political situation and speaks about
panslavism in this context, relating the trend to “the flashes of the national feelings” of the
Slavs. Penetrating the essence of the movement, the writer and publicist emphasizes the presence
of two diff erent currents in it: centralism (Muscovite) and federalism. The Ukrainian
writer is sympathetic to the latter that provides for the opportunity of uniting the Slavic
tribes in order to defend their common interests and includes the principle of mutual respect
and preservation of each national unit’s traditions.
The writer supports his position with such authorities as Mykola Kostomarov, Mykailo
Drahomanov, and others. Franko writes a lot about the role of the Slavophile Brotherhood
of Cyril and Methodius, founded by Kostomarov, and similarity of its program to the posterior
Drahomanov’s one.
Following the thoughts of historians, Franko emphasizes that Slavic peoples feel the
need for “arranging the mutual relationship” because they share common interests. The most
important issue for the Slavs, according to the writer and journalist, is the freedom of every
nation, now limited, in particular by “tsarist despotism”.
“The Slavs can create power — not dangerous to the world, because there is no need in
threatening anyone, but sufficient to secure each national individuality and the greatest freedom
of national and cultural development”, writes the author of the series. Franko dedicates
the final series of texts to the Slovaks and the Czechs.